1982
DOI: 10.1007/bf00238101
|View full text |Cite
|
Sign up to set email alerts
|

Corticotrophin and corticosterone secretion following Δ1-tetrahydrocannabinol, in intact and in hypothalamic deafferentated male rats

Abstract: Adult male rats, either intact (N) or bearing complete hypothalamic deafferentations (CHD), were injected with delta 1-tetrahydrocannabinol (THC: 5 mg/kg BW, IP). Forty-five minutes later, they were decapitated and trunk blood was collected for serum ACTH and corticosterone (CS) determinations. In the N animals, serum levels of both ACTH and CS were markedly elevated in the drug-treated, as compared to the vehicle-treated group (approximately 8-fold and 10-fold, respectively). In CHD rats, on the contrary, THC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…However, other studies demonstrated an elevation in CORT level after administration of cannabinoid receptor agonist in experimental animals [23,24]. Moreover, some studies revealed that administration of cannabinoid receptor agonists activate the HPA axis [25][26][27][28]. In our study, pretreatment of mice with FAAH inhibitor, URB597, or anandamide transport inhibitor, AM404, significantly increased CORT level.…”
Section: Discussionmentioning
confidence: 43%
“…However, other studies demonstrated an elevation in CORT level after administration of cannabinoid receptor agonist in experimental animals [23,24]. Moreover, some studies revealed that administration of cannabinoid receptor agonists activate the HPA axis [25][26][27][28]. In our study, pretreatment of mice with FAAH inhibitor, URB597, or anandamide transport inhibitor, AM404, significantly increased CORT level.…”
Section: Discussionmentioning
confidence: 43%
“…Early studies showed that peripherally administered THC stimulates ACTH secretion (Puder et al, 1982). Later studies showed that the cannabinoid receptors are expressed at the level of both the hypothalamus and pituitary (Herkenham et al, 1991), suggesting that the effects of cannabinoids on the HPA-axis are direct (i.e.…”
Section: Discussionmentioning
confidence: 98%
“…Animals with complete deafferentation of the medio-basal hypothalamus, with markedly depleted content of CRF-41 in the median eminence, did not respond to THC (100). In a recent study we showed that anandamide parallels THC in activating the HPA axis via mediation of a central mechanism which involves the secretion of CRF-41 (131).…”
Section: The Effect Of Hu-210 On the Hpa Axismentioning
confidence: 94%